Indocyanine green-mediated photodynamic therapy on glioblastoma cells in vitro - Ayşe AK; Özgür KAYA; Didem TURGUT COŞAN; Murat GÜLSOY (International Journal of Applied Methods in Electronics and Computers, 2015)
Photodynamic therapy (PDT) is an alternative therapy which is administered with non-toxic drugs, called photosensitizers (PSs) ,  along with irradiation at a specific wavelength of light to damage tumor cells. Different wavelengths of light sources and photosensitizers have been investigated in treatment of many cancer types. In this study, we investigated whether photodynamic therapy using indocyanine green (ICG), also a cyanine dye used in medical diagnostics, can be used to inhibit cell proliferation of glioblastoma. Glioblastoma cells were irradiated with a diode laser ( λ  = 809 nm, 100 J cm −2 ) in continuous wave operation mode. Cell proliferation was measured by XTT assay at 24 h after light irradiation. While only ICG application (10 µg/ml and 50 µg/ml concentrations) had no effects on glioblastoma cell proliferation, ICG in combination with laser irradiation (ICG-PDT) caused a significant decrease of cell proliferation. In conclusion, ICG-PDT may be valuable therapeutic approach as potential treatment for cancer such as glioblastoma. The results could be used as primary data for efficacy of ICG-PDT on malignant tumors.